Advance water abatement in oil and gas reservoir - Sidiq, Hiwa (Curtin University, 2007)
The control of excessive water production in oil and gas producing wells is of increasing importance to the field operator, primarily when trying to maintain the survivability of a mature field from shut in. During the last two decades many chemicals have been studied and applied under the name of relative permeability modifier (RPM) to combat this problem. These chemicals were mostly bullheaded individually into the affected zones, consequently their application resulted in low to medium success, particularly in treating reservoirs suffering from matrix flow. It has been found that the disproportionate permeability reduction depends on the amount of polymer dispersed or absorbed by the porous rock. If single polymers are employed to treat excessive water production in a matrix reservoir they cannot penetrate deep into the formation rock because the polymer will start to build as a layer on the surface of the rock grains. As a result the placement of polymer into the formation will no be piston like and the dispersion over the rock pores will be uneven. To improve water shutoff technology a method of injecting chemicals sequentially is recommended provided that the chemical’s viscosity is increasing successively with the chemicals injected.Experimentally confirmed, injecting chemicals sequentially provides better results for conformance control. The value of post treatment water mobility is conspicuously lowered by the method of applying injecting chemicals sequentially in comparison with the single chemical injection method. For instance, the residual resistance factor to water (Frrw) at the first cycle of brine flushing for this method is approximately five times higher than the Frrw obtained by injecting only one single chemical. Furthermore, for the second cycle of brine flushing Frrw is still higher by a ratio of about 2.5. In addition to this improvement residual resistance factor to oil Frro for this method is less than two which has been considered as the upper limit for conformance control in matrix reservoir. Accordingly injecting chemical sequentially can be applied for enhancing relative permeability modifier performance in matrix reservoir.